If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(m + -5) = 4(m + 1) Reorder the terms: -5(-5 + m) = 4(m + 1) (-5 * -5 + m * -5) = 4(m + 1) (25 + -5m) = 4(m + 1) Reorder the terms: 25 + -5m = 4(1 + m) 25 + -5m = (1 * 4 + m * 4) 25 + -5m = (4 + 4m) Solving 25 + -5m = 4 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 25 + -5m + -4m = 4 + 4m + -4m Combine like terms: -5m + -4m = -9m 25 + -9m = 4 + 4m + -4m Combine like terms: 4m + -4m = 0 25 + -9m = 4 + 0 25 + -9m = 4 Add '-25' to each side of the equation. 25 + -25 + -9m = 4 + -25 Combine like terms: 25 + -25 = 0 0 + -9m = 4 + -25 -9m = 4 + -25 Combine like terms: 4 + -25 = -21 -9m = -21 Divide each side by '-9'. m = 2.333333333 Simplifying m = 2.333333333
| Y=2/x-5 | | 9x+5y=-121 | | 2(K+2)-5(3-2K)=34 | | 4(2y-3)=20 | | 9x+57=-121 | | -9+4(3x-4)=-8-5x | | 15+1=x | | 289/x=17 | | 3-(x+1)=4x+7-5x | | 5-20/5+2*6 | | 6y+9-4y=3 | | 3(a+3)=12 | | ((x^2-2)*(x^2-2))-16(x^2-2)+28=0 | | 5x-9=8-7x | | 3g-2=g+7 | | y=x^2-12+11 | | 3g+2=g+7 | | (x^2-2)-16(x^2-2)+28=0 | | 65=17 | | 3(2x+4)=5(x+5) | | 5(p+3)+3p=39 | | j^2+7j=0 | | 3(x-2)=x | | 7g+3=6g+9 | | m^2-49m=0 | | 3(5-x)=24 | | 2(x-7)=4x | | .3x+.8=1.4 | | 3223323-88292929d=88388d | | d^2-4d-4=d+6 | | 3(6)+7=24 | | b/8-17=13 |